2007
DOI: 10.1123/jsep.29.2.147
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Task Constraints on Visual Search Behavior and Decision-Making Skill in Youth Soccer Players

Abstract: We examined differences in visual search behaviors and decision-making skill across different microstates of offensive play in soccer using youth participants (13.0-15.8 years) varying in skill and experience. We used realistic film simulations of offensive play, movement-based response measures, and an eye movement registration technique. Playing experience, skill level, and the unique constraints of the task, expressed by the number of players and relative proportion of offensive and defensive players, deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
191
2
38

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(243 citation statements)
references
References 29 publications
12
191
2
38
Order By: Relevance
“…Experts are able to rapidly extract meaningful chunks of structured information from a visual scene (Helsen and Pauwels 1992;Helsen and Starkes 1999), though the patterns of gaze that underpin these behaviours appear to be very context specific. For instance, skilled athletes may rely on a lower search rate (ie fewer fixations per second) in some decision-making tasks (eg Bard and Fleury 1976;Helsen and Pauwels 1992), but show a higher search rate in other tasks (eg Mann et al 2009;Vaeyens et al 2007a;Williams et al 1994). The ideal search pattern also apparently varies when an identical task-for example, anticipating a soccer pass-is coupled with variations in the number of players in the scene (Williams and Davids 1998;Williams et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Experts are able to rapidly extract meaningful chunks of structured information from a visual scene (Helsen and Pauwels 1992;Helsen and Starkes 1999), though the patterns of gaze that underpin these behaviours appear to be very context specific. For instance, skilled athletes may rely on a lower search rate (ie fewer fixations per second) in some decision-making tasks (eg Bard and Fleury 1976;Helsen and Pauwels 1992), but show a higher search rate in other tasks (eg Mann et al 2009;Vaeyens et al 2007a;Williams et al 1994). The ideal search pattern also apparently varies when an identical task-for example, anticipating a soccer pass-is coupled with variations in the number of players in the scene (Williams and Davids 1998;Williams et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Además hay evidencias que sugieren que la información puede ser procesada de forma más rápida por la visión periférica que con la vía fóvea, lo que puede aportar una ventaja significativa cuando los tiempos para decidir son bajos (Vaeyens et al, 2007a), como …”
Section: Discussionunclassified
“…Por tanto en situaciones de tiempo restringido, los jugadores hábiles usan, además de las fijaciones centralizadas, la visión periférica para extraer información de las posiciones y movimientos de los jugadores (Vaeyens et al, 2007a).…”
Section: C D D E P O R T Eunclassified
See 1 more Smart Citation
“…This divergence might be explained due to group's characteristics. Indeed, Vaeyens et al [32] studied differences in responses accuracy between soccer players and non-players [very distinctive groups) and found that the first ones made more accurate decisions. Therefore, the game complexity differs according to the age group and specific experience as left-side attacker, thus requiring the appropriation of decision-making and performance to their play level.…”
Section: Discussionmentioning
confidence: 99%